Reliability of sitting posture between physical therapist video-based evaluation and SMART IMU system using rapid upper limb assessment (RULA) - Ratikanlaya Tanthuwapathom; Udomporn Manupibul; Wimonrat Jarumethitanont; Weerawat Limroongreungrat; Songpol Ongwattanakul; Warakorn Charoensuk (Scientific Reports)
Abstract This study investigates the ergonomic assessment of sitting postures and the potential for work-related musculoskeletal disorders (WMSDs) in office environments by comparing traditional physical therapist evaluations with Inertial Measurement Unit (IMU) technology by determining the reliability and accuracy of sitting posture assessment using the rapid upper limb assessment (RULA) method. In this experiment, neck and body angle data is collected from twenty participants while sitting and working. The study aims to capture and compare the neck and trunk posture score based RULA protocol system to evaluate ergonomic risks. The findings revealed a strong correlation between the video-based evaluations by the physical therapist and the data obtained from the SMART IMU system, demonstrating the feasibility of using these combined approaches for ergonomic assessments. The results highlight the effectiveness of integrating traditional ergonomic assessment tools with modern IMU technology in comprehensively analyzing the ergonomic risks associated with prolonged sitting.